Comparison of TENS electrodes and textile electrodes for electrocutaneous warning - Eva-Maria Dölker; Yasemin Cabuk; Tino Kühn; Jens Haueisen (PLoS ONE, 2025)
Electrocutaneous stimulation can be employed to alert workers in potentially hazardous situations. Previous parameter studies used TENS electrodes during the developmental process of the electrical warning system. As a step towards more practicability, we now focus on electrocutaneous stimulation through wearable textile electrodes. In order to determine the feasibility of a novel textile electrode cuff in comparison to previously used TENS electrodes, two studies were conducted. In a study on n = 30 participants, perception, attention, muscle twitch, and intolerance thresholds as well as qualitative and spatial perceptions, were determined for eight pairs of electrodes circumferentially placed around the upper right arm for TENS and for textile electrodes. In a second study on n = 36 participants, these thresholds were also determined during vibration, and a warning signal pattern was presented during vibration. We found smaller perception thresholds for the textile electrodes in comparison to the TENS electrodes for all 8 electrode pairs and occasional differences for the attention and intolerance thresholds, which might be mainly explained by the varying electrode sizes due to the manual production process of the textile electrodes. Stimulation using textile electrodes within the cuff showed less frequent muscle twitches compared to TENS electrodes. Other qualitative and spatial perceptions appeared comparable. The perception, attention, and intolerance thresholds increased during vibration comparable to previous results with TENS electrodes. The feasibility of using the textile electrodes during vibration and for the application of a warning signal was successfully demonstrated. Occasional cases occurred where the transition impedance was too high while using the textile electrodes. Future studies will focus on electrode optimization to achieve a wearable solution with both low electrode-skin transition impedance and minimal muscle twitching.